The effectiveness of anaerob-aerob bio filters and phytoremediation using Pistia Stratiotes for reducing COD and BOD5 content in laundry liquid waste - Zulkhairi Zulkhairi; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The laundryliquid waste is rich in COD and BOD5 and thus need to be processed before being flown to environment. A study aims to reduce the COD and BOD5 in that waste has been conducted in January – March 2018. The waste (135 L) was treated using a batch system that was consisted of 2 aerob and 2 anaerob tanks and a Pistia Stratiotesphytoremediation pond. The liquid waste was kept for 10 days in anaerob tanks, 7 days in aerob tanks and 15 days in phytoremediation pond. By the end of the experiment, the COD reduced from 1.440 mg/l to 110 mg/l (the effectiveness was of 92.36%). While the BOD5 reduced from 510 mg/l – 55 mg/l (the effectiveness was 89.21%). Other water quality parameters such as pH was normal and DO was improved. The treated waste was used for rearing Oreochromis niloticus (3-4 cm TL) and was kept for 15 days. The survival rate of the fish was 100%. Based on data obtained, it can be concluded that the combination of bio filters and phytoremediation system using Pistia Stratiotesis effective to reduce the COD and BOD5 content in the laundry liquid waste. Keyword : waste water, detergent contaminated waste, batch system, waste management